Development of Moodle-based Physical Education Learning Media in Junior High Schools During the Pandemic - Haaq, Ardiyan Naafi Hafizh; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Mohamad Roil (Jurnal Abdimas Kartika Wijayakusuma, 2022)
The occurrence of the COVID-19 pandemic has had a major impact on education in Indonesia. Various efforts were made to attract students' interest in learning, one of the efforts made by the teacher was learning media with the aim that students were able to understand the lesson. Therefore, there is a need for a new idea to improve the quality of education during this pandemic. The purpose of this study was to determine the effectiveness of the Moodle learning media application as a means of learning sports for junior high school students during a pandemic. After seeing the results of the activities above, it is necessary to have varied learning to increase the literacy level of students. The results of this study showed an increase in students' knowledge at the time of the post-test 68% increased to 88% after the post-test data was obtained.